Response of Planting Medium Compotition and Watering Interval to Growth of Green Deli Rose Apple Seedling (Sygizium samarangense) - Frans Julianta Karo-karo (Universitas Sumatera Utara, 2016)
The purpose of this research is to deferinte the response of planting medium compotition and watering interval to growth of Green Deli Rose Apple hijau seedling (Sygizium samarangense). The study was conducted at green house of the Faculty of Agriculture, University of North Sumatra, Medan with the altitude 25 m above sea level, from July to October 2014. This research was used split plot design with two treatments, watering interval as the main plot treatment with 3 category: I1 (one day watering interval), I2 (three days watering interval), I3 (five days watering interval) with compotition of planting medium as subplot with 4 category : M1 (subsoil), M2 (subsoil+charcoal (2:1), M3 (subsoil+charcoal (1:1), M4 (subsoil+charcoal (1:2) with 3 replication. The result showed the treatment of planting media compotition has asignificant to increasing of : stem diameter and root volume and watering interval has a significantly affected to increasing of seedling height, stem diameter, number of leaves, root volume, number of root and number of primer branch. The interaction has a significantly affect to increasing of root volume parameter.